Methanolic extract of Morinda citrifolia Linn. unripe fruit attenuates methamphetamine-induced conditioned place preferences in mice - Pandy, Vijayapandi; Chang, Wai Yew; Roslan, Nurul Fatin Amira; Sajat, Arif; Abdulla Jallb, Abdulla Hamid; Vijeepallam, Kamini (Elsevier, 2018)
The first objective of the present study was to determine the appropriate dose of methamphetamine (Meth) to induce a successful conditioned place preference (CPP) in mice. The next objective was to examine the effect of a methanolic extract of M. citrifolia unripe fruit (MMC) against Meth-induced CPP in mice. In answering to the first objective, following the preconditioning test, an intraperitoneal injection of a fixed dose of Meth (0.5 or 1 or 2 mg/kg, i.p.) or saline (10 ml/kg, i.p.) was given on alternate days during the 10 days conditioning period followed by a postconditioning test conducted in Meth-free state. The first experiment revealed that 0.5 mg/kg of Meth could be an appropriate fixed low dose to induce CPP in mice. Meanwhile, in other experiments, the effect of MMC and bupropion (BUPR) against the expression, extinction, and reinstatement of Meth (0.5 mg/kg)-induced CPP in mice, respectively, was investigated. In a separate set of studies on each phase, an oral administration of MMC (1, 3 and 5 g/kg, p.o.) or BUPR (20 mg/kg, p.o.) was given 60 min prior to CPP postconditioning testing or extinction testing or reinstatement testing in mice. Extinction trials were conducted in Meth-free state to weaken CPP over the next 5 days. Reinstatement test was conducted by a single low dose priming injection of Meth (0.1 mg/kg, i.p.). The present study, however, failed to establish a successful extinction and reinstatement of Meth-CPP in mice. Further studies using other doses of Meth are warranted for a successful establishment of all phases of Meth CPP in mice. This study also demonstrates that MMC (3 and 5 g/kg, p.o.) and BUPR (20 mg/kg, p.o.) could attenuate the expression of Meth-induced CPP in mice.